2020
DOI: 10.1007/s00392-020-01766-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism in patients with COVID-19: characteristics and outcomes in the Cardio-COVID Italy multicenter study

Abstract: Background Pulmonary embolism (PE) has been described in coronavirus disease 2019 (COVID-19) critically ill patients, but the evidence from more heterogeneous cohorts is limited. Methods Data were retrospectively obtained from consecutive COVID-19 patients admitted to 13 Cardiology Units in Italy, from March 1st to April 9th, 2020, and followed until in-hospital death, discharge, or April 23rd, 2020. The association of baseline variables with computed tomography-confirmed PE was investigated by Cox hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 30 publications
3
41
4
4
Order By: Relevance
“…Our findings might be explained by the fact that DOAC therapy acts only on the coagulation cascade without the additional anti-inflammatory and endothelial-protection properties associated with heparin that could be particularly useful in this specific setting of patients [ 25 , 26 ]. In line with our results, a recent retrospective study by Ameri et al [ 27 ] reported that an oral anticoagulant therapy prior to the admission for COVID-19 tended to be more frequent among patients who eventually suffered from PE, suggesting a lingering pro-thrombotic status despite oral anticoagulant therapy in this subgroup of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings might be explained by the fact that DOAC therapy acts only on the coagulation cascade without the additional anti-inflammatory and endothelial-protection properties associated with heparin that could be particularly useful in this specific setting of patients [ 25 , 26 ]. In line with our results, a recent retrospective study by Ameri et al [ 27 ] reported that an oral anticoagulant therapy prior to the admission for COVID-19 tended to be more frequent among patients who eventually suffered from PE, suggesting a lingering pro-thrombotic status despite oral anticoagulant therapy in this subgroup of patients.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that efficacy and side effects balanced for lopinavir (giving a null net effect on mortality) but not for darunavir (giving a net negative effect). Of interest, in an Italian cohort of 689 COVID-19 hospitalized patients followed for negative outcomes ( 39 ), it was found that the incidence of in-hospital pulmonary embolism was higher in patients using DRV/c but not LPV/r. On the contrary, other studies did not find an increased rate of severe adverse effects associated with DRV/c ( 28 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, anti-inflammatory therapies and thromboprophylaxis have been the mainly studied drugs for COVID-19 (51)(52)(53)(54). Dexamethasone was found to be associated with lower 28-day mortality in the controlled, open-label Randomized Evaluation of COVID-19 Therapy (RECOVERY) trial (51).…”
Section: Indirect Mechanismsmentioning
confidence: 99%